Perilaku Pengunjung dalam Memanfaatkan Fungsi Ruang Publik di Area Monumen Ground Zero Legian Kuta - Adnyana Putra, I Wayan Yogik (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2017)
Ground Zero Monument is a remembrance for Bali bombing attack that took place on October the 12 th 2002. Its development however has invited various unanticipated informal activities such as those entail food vendors' effort to sell their products and the use of the surrounding sidewalks as sitting areas by tourists and visitors. These have in subsequence reduced the scale of public space surrounding the Monument and thus hindered the comfort of pedestrians who use the sidewalks. The main objective of this research is to examine behavioral patterns of visitors in using public space available around the Ground Zero Monument . This research applied qualitative descriptive method. It indeed concludes several findings. First, the use of public space surrounding the monument takes place at certain times only. Second, there are two types of behaviors takes place: innate (natural) and imitative behaviors. Reasons behind these behaviors include personal; situational, cultural, and space availability factors. Keywords: behavior, public space, innate, imitative, Ground Zero Monument